Digital Curriculum Integration and Learning Quality in Higher Education: Evidence from a Cross Sectional Survey in West Java, Indonesia - Purwadhi Purwadhi; Ade Mubarok (Sakura Digital Nusantara, 2026)
Purpose: This study examines why digital curriculum integration has become essential for improving learning quality in higher education, particularly in the context of rapid educational digitalization in West Java, Indonesia. It argues that the effectiveness of digital transformation depends not only on technology adoption, but on the strategic integration of digital tools into curriculum design, instructional delivery, learning activities, and assessment. Methods: The study employed a quantitative cross-sectional survey design involving 356 lecturers and undergraduate students from selected public and private higher education institutions in West Java. Data were collected through a structured questionnaire and analyzed using descriptive statistics, validity and reliability testing, Pearson correlation, and structural model analysis to test the relationships among digital curriculum integration strategy, lecturers’ digital competence, institutional support and digital infrastructure, and learning quality. Findings: The results show that digital curriculum integration strategy had a positive and significant effect on learning quality (β = 0.421, p < 0.001). Lecturers’ digital competence significantly influenced digital curriculum integration (β = 0.368, p < 0.001), while institutional support and digital infrastructure significantly strengthened the relationship between digital curriculum integration and learning quality (β = 0.187, p = 0.001). The model explained 54.8% of the variance in learning quality. Research implications: The cross-sectional design and self-reported data limit causal inference and may affect generalizability beyond West Java. Originality: This study contributes by positioning digital curriculum integration as a strategic pedagogical and institutional approach to improving higher education learning quality in a regional Indonesian context.